"Prevention is better than cure": challenges in engaging employees through gamification. Issue 2 (2nd September 2021) - Gupta, Manish; Behl, Abhishek; Kumar, YLN
Abstract : Purpose: Gamification, the use of game elements and techniques in the non-game contexts, is gaining popularity among human resources (HR) in an online mode. This paper intertwines the flow and engagement theories to know the challenges faced by companies in India in implementing gamification in their various HR practices to engage their employees. Design/methodology/approach: Semi-structured interviews of only the information-rich cases including game designers and HR practitioners were conducted using snowball sampling technique. The interviews were transcribed and were analysed using thematic analysis. Findings: Three reviewed themes emerged from the data labelled as organization-, employee- and job-specific factors. Separate thematic maps drawn for each of the reviewed themes give particulars pertaining to the issues highlighted by the game designers and the HR practitioners in gamification. Practical implications: The results of the study are expected to help the organizations make an informed decision about whether they should go ahead with risking their resources as they expect improved engagement levels at work. Originality/value: The findings contribute to the online engagement literature by exploring its antecedents in the context of gamification of HR practices for higher engagement at work.